The Struggle to Constitute and Sustain Productive Orders: Vincent Ostrom's Quest to Understand Human Affairs - Sproule-Jones, Mark,; Allen, Barbara,; Sabetti, Filippo, (Lexington Books, 2008)
Countries, governments, and organizations devise constitutions to reflect their visions of governance and rules for their leaders. They vary considerably in both formats and consequences. Disputes over constitutions can lead to fights, contests, debates, and more. Vincent Ostrom is one of America's leading scholars on constitutions and has spent a lifetime researching, analyzing, and writing about constitutions in America and overseas. He provides methods to judge and to implement constitutions as citizens struggle with their formulation. In this book, scholars from around the world add to this intellectual quest of massive scholarly and practical importance. Using the research and methodology pioneered by Ostrom, they identify and analyze the criteria for successful constitutions in both theory and practice.